Improved protection of outdoor workers from solar ultraviolet radiation: position statement. (21st November 2020) - John, S.M.; Garbe, C.; French, L.E.; Takala, J.; Yared, W.; Cardone, A.; Gehring, R.; Spahn, A.; Stratigos, A.
Abstract: The vast majority of non‐melanoma skin cancer (NMSC) is attributable to excessive exposure to ultraviolet radiation (UVR). Outdoor workers are exposed to an UVR dose at least 2 to 3 times higher than indoor workers and often to daily UVR doses 5 times above internationally recommended limits. The risk of UVR workplace exposure is vastly neglected, and the evident future challenges presented in this statement are contrasted with the current situation regarding legal recognition, patient care and compensation. While prevention is crucial to reduce cancer risks for outdoor workers, it is as much of relevance to better protect them through legally binding rules and regulations. Specific actions are outlined in five recommendations based on a Call to Action (table 1). The role of health professionals, including dermatologists, in this context is crucial.